Efeito de produtos de acabamento na cor de madeiras da caatinga - Maia, Juliana Holanda (Universidade Federal Rural do Semi-Árido, 2018)
Know to color of woods from Caatinga region is important for being able to indicate new applications and products with greater added value. Wood extractives can be responsible for color, smell, taste, density, among other characteristics. Specially wood color is essential for acceptance in any environment. Based on that, the aim of this work was do characterization e correlation of color and chemical properties of woods from Angico (Anadenanthera colubrina var. cebil (Griseb.) Altschul), Cajueiro (Anacardium occidentale L.), Jurema de Embira (Mimosa ophthalmocentra Mart. ex Benth.), Pereiro (Aspidosperma pyrifolium Mart.) and Sabiá (Mimosa caesalpiniifolia Benth). This work also aimed evaluate the effect of three finishing products (varnish, polistain and sealant) in the wood color of the five species. The results of the correlation showed that the red pigment of the wood is influenced by the components that can be extracted by hot water and acetone, while yellow pigments are mainly affected by lipophilic substances. About finishing products, the polistain showed a higher adherence among the studied species. But when keep the original wood color is desired, it was indicate the use of varnish or sealant for Pereiro e Sabiá and polistain for Cajueiro.
Keywords: Caracterização Química; Colorimetria; Verniz; Polistain; Selador; Chemical Characterization; Colorimetry; Varnish; Polistain; Sealant; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL